Key Drivers of Cruelty-Free Cosmetics: Mediating Role of Purchase Intention - Phuong Viet Le-Hoang; Hao Huynh Nguyen (Emerging Science Journal)
This study aims to explore the factors influencing the purchase decisions of cruelty-free cosmetics, focusing on the mediating role of purchase intention. The objectives include evaluating the impact of internal factors (attitude, altruism, environmental knowledge) and external factors (social media, subjective norms) on purchase intention and decision-making. Structural equation modeling (SEM) analyzes the data from a survey of 199 participants to test the relationships between variables. Findings show that internal factors, especially altruism and environmental knowledge, have a stronger influence on purchase intention compared to external pressures from social media and subjective norms. The results indicate that personal beliefs play a vital role in shaping consumers' ethical purchase behavior. This study provides practical insights for cosmetic brands, suggesting that campaigns emphasizing environmental awareness and animal welfare can boost purchase intentions. The novelty of the research lies in differentiating the impacts of internal and external factors, highlighting that consumers prioritize personal values over social influences when making ethical purchasing decisions. The study also offers managerial implications, recommending that brands enhance consumer engagement through educational campaigns to foster long-term commitment to cruelty-free products.